Degradation of crude oil in a co-culture system of Bacillus subtilis and Pseudomonas aeruginosa - Wu, Bo; Xiu, Jianlong; Yu, Li; Huang, Lixin; Yi, Lina; Ma, Yuandong (Frontiers in Microbiology, 2023)
Microbial remediation has been regarded as one of the most promising decontamination techniques for crude oil pollution. However, there are few studies on the interaction of bacteria in the microbial community during bioremediation. The aim of this work was to research the promotion of defined co-culture of Bacillus subtilis SL and Pseudomonas aeruginosa WJ-1 for biodegradation of crude oil. After 7 days of incubation, the analysis of residual oil, saturated and aromatic fraction in the samples showed that the degradation efficiency of them was significantly improved. The degradation efficiency of crude oil was enhanced from 32.61% and 54.35% in individual culture to 63.05% by the defined co-culture of strains SL and WJ-1. Furthermore, it was found that the defined co-culture system represented relatively excellent performance in bacterial growth, cell surface hydrophobicity (CSH) and emulsification activity. These results indicated that the combination of Bacillus subtilis and Pseudomonas aeruginosa can effectively promote the degradation and utilization of crude oil, which may provide a new idea for the improvement of bioremediation strategies. GRAPHICAL ABSTRACT